2004
DOI: 10.1016/j.abb.2004.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles in rat intestine identify pathways for 1,25-dihydroxyvitamin D3 stimulated calcium absorption and clarify its immunomodulatory properties

Abstract: Microarray technology has been used to discover 1,25-dihydroxyvitamin D(3) (1,25-(OH)(2)D(3)) induced gene expression changes in rat small intestine in vivo. Here, we report gene expression changes related to intestinal absorption or transport, the immune system and angiogenesis in response to 1,25-(OH)(2)D(3). Vitamin D deficient rats were intrajugularly given vehicle or vehicle containing 730 ng of 1,25-(OH)(2)D(3)/kg of body weight. Intestinal mRNA was harvested from duodenal mucosa at 15 min, 1, 3, and 6 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 87 publications
4
85
0
Order By: Relevance
“…The lack of VDR transcripts and proteins in the intestine of VDRKO mice was confirmed by RT-PCR and immunoblot experiments ( Figures 1A and 2, A and C; data not shown). As shown in Figure 1, A and B, expression levels of Cldn3 transcripts were higher in the jejunum in VDRKO mice than in WT mice, in good agreement with the finding that the gene expression of Cldn3 is decreased in the rat small intestine after 1␣,25(OH) 2 D 3 treatment (Kutuzova and Deluca, 2004). In contrast, the mRNA expression of Cldn2 and Cldn12, but not Cldn7 or Cldn15, was reduced in the VDRKO mouse jejunum compared with that of the WT mouse (ϳ3-and 4-fold decreases, respectively).…”
Section: Claudins 2 and 12 Are Down-regulated In The Intestine Of Vdrsupporting
confidence: 75%
“…The lack of VDR transcripts and proteins in the intestine of VDRKO mice was confirmed by RT-PCR and immunoblot experiments ( Figures 1A and 2, A and C; data not shown). As shown in Figure 1, A and B, expression levels of Cldn3 transcripts were higher in the jejunum in VDRKO mice than in WT mice, in good agreement with the finding that the gene expression of Cldn3 is decreased in the rat small intestine after 1␣,25(OH) 2 D 3 treatment (Kutuzova and Deluca, 2004). In contrast, the mRNA expression of Cldn2 and Cldn12, but not Cldn7 or Cldn15, was reduced in the VDRKO mouse jejunum compared with that of the WT mouse (ϳ3-and 4-fold decreases, respectively).…”
Section: Claudins 2 and 12 Are Down-regulated In The Intestine Of Vdrsupporting
confidence: 75%
“…We and others suggested the involvement of vitamin D in the regulation of paracellular calcium transport in the intestine (6,7,19,20). From a microarray study in rats, it seemed likely that vitamin D regulates tight junction permeability in intestine by regulating expression of several tight junction proteins including claudin-3 (6).…”
Section: Discussionmentioning
confidence: 99%
“…Because this hormonal form of vitamin D is regulated in response to the need for calcium, it became clear that the endogenous factor discovered by Nicolaysen and Egg-Larsen is the vitamin D endocrine system producing the final vitamin D hormone, 1,25-(OH) 2 D 3 (4,5). There is still debate whether vitamin D further influences the diffusional component of calcium absorption, taking place at high intestinal levels of calcium (6,7).…”
Section: Microarrays ͉ Trpv6 Ko Mice ͉ Vitamin D ͉ Vitamin D Mechanismentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of calbindin-D is induced by dihydroxycholescalciferol (1,25-(OH) 2 D 3 ). 6) Low luminal calcium up-regulates the active transport by increasing the CaT1 and ECaC1 mRNA. 7,8) Researchers have also found that the intestinal calcium absorption can be enhanced by various food factors.…”
mentioning
confidence: 99%